2009
DOI: 10.1590/s1982-56762009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic diversity of Magnaporthe oryzae from leaves and panicles of rice in commercial fields in the State of Goiás, Brazil

Abstract: Genetic and phenotypic structure of Magnaporthe oryzae populations of two upland rice cultivars was determined. Monoconidial isolates were obtained from rice blast affected fields, four from cv. BRS Bonança and four from cv. Primavera, in Goias State (2001)(2002)(2003). The pathotypes IB-41 and IB-9 were predominant in both leaf and panicle isolates of BRS Bonança and IF-1 in Primavera. A great majority of pathotypes were common to both leaf and panicle subpopulations of Bonança (42.8%) and Primavera (66.6%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(25 reference statements)
0
8
0
4
Order By: Relevance
“…The results showed a high level of genetic diversity, and blast strains could be clustered based on geographic distribution and collection time. Silva et al [18] used rep-PCR analysis with two primer sequences from Pot2 to assess genetic diversity of rice blast strains from Brazil. Xu et al [19] used RAPD, REMAP, rep-PCR markers, and AVR gene sequences to examine the genetic diversity of rice blast fungus strains from China.…”
Section: Genetic Diversity Of Pyricularia Oryzae Using Srap and Issr mentioning
confidence: 99%
“…The results showed a high level of genetic diversity, and blast strains could be clustered based on geographic distribution and collection time. Silva et al [18] used rep-PCR analysis with two primer sequences from Pot2 to assess genetic diversity of rice blast strains from Brazil. Xu et al [19] used RAPD, REMAP, rep-PCR markers, and AVR gene sequences to examine the genetic diversity of rice blast fungus strains from China.…”
Section: Genetic Diversity Of Pyricularia Oryzae Using Srap and Issr mentioning
confidence: 99%
“…The first results indicated that each locus had a range of different alleles from 2 to 10 and the results of SSR showed genes which were polymorphic in nature [Liu et al 2008]. Silva et al [2009] evaluated the genetic diversity of P. grisea on rice in Brazil. The genetic analysis of isolates showed the highest genetic diversity population belonged to 103 haplotypes in Bonanca and 49 in Primavera.…”
Section: Introductionmentioning
confidence: 99%
“…This fungus is considered as highly variable and high degree of pathogenic variation (pathotypes) is observed in the field [8,9]. Sexual reproduction can enhance and influence the genotypic variability of M. oryzae populations where the recombinant progenies may have new capability to infect different host cultivars.…”
Section: Introductionmentioning
confidence: 99%